An Index Theorem for General Equilibrium Models with Production - Kehoe, Timothy J. (Econometrica, 1980)
[In this paper we prove a global index theorem for general equilibrium models with activity analysis production technologies. We begin by constructing a single-valued function whose fixed points are equivalent to the equilibria of such a model. We then associate each fixed point with an index that is an integer determined by the local properties of this function at that point. The global index theorem makes a statement about the sum of all the indices of equilibria that implies conditions sufficient for uniqueness of equilibrium.]